Study of the influence of the type of matrix used in carbon-epoxy composites on fatigue delamination under mode III fracture. (15th January 2020) - Bertorello, C.; Viña, J.; Viña, I.; Argüelles, A.
Abstract: The fatigue delamination process of three different aeronautical quality composites subject to mode III fracture loading is studied experimentally in this paper with the aim of analysing the effect of the type of matrix used under this fatigue fracture mode. In all cases, the main difference between the composite materials considered in this study is the type of epoxy resin used as the matrix. The test method used to produce the delamination process under mode III fracture is known as the Longitudinal Half Fixed Beam (LHFB) method, used in previous studies by the authors, which was shown to be a valid method for generating the delamination process in composite sheet materials subject to mode III fatigue loading. The experimental data from the fatigue tests were treated with a probabilistic model based on the Weibull distribution. This model facilitates the identification of relevant aspects of the fatigue behaviour of these materials, such as the estimation of fatigue strength for periods of time greater than those tested here, as well as the reliability of the results. The results thus obtained reflect important differences in the fatigue behaviour of the materials under study, the type of matrix being the predominant parameter of the fracture process under mode III loading. Graphical abstract: Unlabelled Image Highlights: The Longitudinal Half Fixed Beam device is valid for obtaining the values of both static and dynamic energy release rates Fracture toughness depends on the matrix but its behaviour varies depending on the type of stress to which it is subjected The most typical fractography in mode III-fatigue is formed by cusps with a preferred orientation at 45° and resin beds